Rubber-pad forming processes : technology and applications - Ramezani, Maziar; Ripin, Zaidi M.; ScienceDirect eBooks (Cambridge : Woodhead Pub., 2012)
This book describes different types of rubber-pad forming processes currently being studied for their experimental and numerical advantages and disadvantages. Rubber forming adopts a rubber pad contained in a rigid box in which one of the tools (die or punch) is replaced by the rubber pad. Up to 60% of all sheet metal parts in aircraft industry such as frames, seat parts, ribs, windows and doors are fabricated using rubber-pad forming processes. Key process parameters such as rubber material, stamping velocity, rubber-pad hardness and thickness and friction conditions are investigated. The potential role of rubber as a flexible punch in metal working processes is to give insight to engineers about different parts that can be produced using this processThe procedure of suitable die design for each process is presented in detailFull defect analysis is undertaken with a thorough report presented to optimize rubber-pad forming processes.
9.7 Bibliography10 Tube bulging using rubber rods; 10.1 Introduction; 10.2 Tube end bulging; 10.3 Bulging at the middle of a tube; 10.4 T-branch forming; 10.5 Theory of axisymmetric tube bulge forming; 10.6 Other tube bulging processes; 10.7 Bibliography; 11 Conclusions; Combined bibliography; Index.
Includes bibliographical references and index.
Elsevier
Keywords: Sheet-metal work; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; Sheet-metal work; Electronic books